Geflecht aus 81 Büchern - Zur variantenreichen Gestalt des äthiopischen Bibelkanons - Brandt, Peter (Aethiopica, 2000)
The canon lists in Sēnodos und Fetḥa nagaśt do not represent the original arrangement of biblical books, since they go back to coptic traditions. Most of the biblical manuscripts are younger than the lists (c. 14 to c. 20), and their order of books is very disparat. Although the original arrangement cannot be identified from them, they reveal aspects of arrangement, which generate a specific ethiopian shape of the bible. Books or groups of books are bound together in different ways. In the OT there are eight books of the Law instead of five, and the rest remains in great variance. In the NT the internal order of the groups is stable, but the arrangement of the groups varies. Looking at this variability from a perspective of reception, the manuscripts are important, for they show what the believing community actually had before it. The ethiopian biblical canon seems to be construed as a net of various innerbiblical dialogues.